The Trump Election in 2016: The impact of social networks and socio-economic conditions - Dos Santos, Maria José Palma Lampreia (2021)
This paper aims to determine the role of social media and socio-economic conditions in the election of Donald Trump as a President of the United States in 2016. The methodology was based on quantitative and qualitative analysis, as well as, a huge systematic revision on the subject. The main conclusions show that voters ‘expectations based on the results of social media and, on the other hand, on their socioeconomic conditions, were influenced by the adoption of populist attitudes by the promoters of this electoral campaign. For consequence will be necessary to deepen the knowledge on this topic, its fundamentals and its impacts.